Gene expression patterns in Fraxinus excelsior clones with contrasting susceptibility to Hymenoscyphus fraxineus - Eshghi Sahraei, Shadi (SLU/Dept. of Forest Mycology and Plant Pathology, 2016)
This study aimed at investigating gene expression patterns in resistant and susceptible clones of Fraxinus excelsior L. (European ash) in response to infection with Hymenoscyphus fraxineus. A further objective of this study was to investigate the role of ABA8-hydroxylase genes (ABA8H) in European ash under infection with H. fraxineus. To address the first aim, bark of susceptible and resistant clones were infected with H. fraxineus and samples were taken after 9 months from the margins of necrosis. Total RNA was extracted and sequenced by next generation Illumina sequencing technique. To identify differentially expressed genes (DEGs), sequences were aligned to the European ash draft genome before analyzing in the Cufflinks pipeline. The DEGs were then annotated in Blast2go. More than 87,000 transcripts were presented in the library. In the inoculated susceptible clones, up-regulation of the 2-hydroxyisoflavanone dehydratase-like (HID) gene, associated with formation of secondary metabolites, was observed. The over expression of caffeoyl- o- methyltransferase (COMT) and farnesyl diphosphate synthase was also detected in the inoculated susceptible clones. In the inoculated resistant clones, the defense response genes such as 1-aminocyclopropane-1-carboxylate oxidase (ACC), some of the ethylene-responsive transcriptional factors (ERFs) and WRKY- transcriptional factors (TFs) were up-regulated. The peroxidase-like and pathogen- related protein (PR) genes, secoisolariciresinol dehydrogenase-like, flavonol syn- thase flavanone 3-hydroxylase-like, phenylalanine ammonia-lyase and shikimate chloroplastic-like genes were up-regulated but ERFs were down-regulated in both susceptible and resistant clones in response to H. fraxineus inoculation. Shikimate chloroplastic-like acts in the secondary metabolite pathway just like flavonol syn- thase flavanone 3-hydroxylase-like. To address the second aim, susceptible genotypes of the European ash were subjected to biotic stress which included wounding and inoculation with H. fraxineus. RNA was extracted from lesions and expression of candidate genes, i.e. three ABA8H genes and two encoding NAC-TFs was quantified. Some NAC genes are known to have a role in abscisic acid (ABA) signaling pathway. The European ash ABA8H and NAC genes were up-regulated 1 day after inoculation but already by day 7, they had been down-regulated. It is possible that the NAC genes contribute to the ABA biosynthesis pathway and thereby play roles in the defense mechanism.